2018
DOI: 10.1021/acs.analchem.8b00914
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Enrichment of Extracellular Vesicles from Biological Fluids

Abstract: Extracellular vesicles (EVs) have emerged as a rich source of biomarkers providing diagnostic and prognostic information in diseases such as cancer. Large-scale investigations into the contents of EVs in clinical cohorts are warranted, but a major obstacle is the lack of a rapid, reproducible, efficient, and low-cost methodology to enrich EVs. Here, we demonstrate the applicability of an automated acoustic-based technique to enrich EVs, termed acoustic trapping. Using this technology, we have successfully enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 42 publications
2
100
0
Order By: Relevance
“…Various approaches have been tested for isolating EVs. A recent article described the use of creating a standing wave in a microfluidic chamber (Figure ). Polystyrene beads are used as seeding particles, which are retained in the standing wave.…”
Section: Methods For Isolation/characterization Of Evs From the Gcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been tested for isolating EVs. A recent article described the use of creating a standing wave in a microfluidic chamber (Figure ). Polystyrene beads are used as seeding particles, which are retained in the standing wave.…”
Section: Methods For Isolation/characterization Of Evs From the Gcfmentioning
confidence: 99%
“…Various approaches have been tested for isolating EVs. A recent article described the use of creating a standing wave in a microfluidic chamber 30 (Figure 2 F I G U R E 1 Detection of EVs using the ExoView platform (NanoView Biosciences) utilizing specific labelling of EVs, bound to the surface with CD63 antibody, and detected with fluorescently tagged anti-CD63 antibody. A, Schematic of NanoView Biosciences detection system.…”
Section: Microfluidics and Nanofluidicsmentioning
confidence: 99%
“…Still, the same miRNAs could be found in comparable concentrations of EVs in urine and serum samples in a comparison of both isolation methods. This suggests that the amount of EVs isolated by acoustic trapping might be sufficient for diagnostic purposes [135]. Another study revealed that the RNA yield of EVs from an equivalent of 1.7 mL urine is sufficient to generate a NEXTflex cDNA library for Illumina Next Generation Sequencing (NGS) of miRNAs.…”
Section: Acoustic Trappingmentioning
confidence: 99%
“…Another study revealed that the RNA yield of EVs from an equivalent of 1.7 mL urine is sufficient to generate a NEXTflex cDNA library for Illumina Next Generation Sequencing (NGS) of miRNAs. Hence, this method represents a fast, automated alternative to ultracentrifugation [109,135]. The method was further improved by combining an acoustic trap and a microfluidic chip.…”
Section: Acoustic Trappingmentioning
confidence: 99%
“…125,147 More recently, enrichment of EVs from biological fluids was achieved using tilted-angle standing sequential surface acoustic wave (taSSAW) 181 and beadmediated acoustic trapping. [182][183][184] As was mentioned in Section 1.3, separation in acoustophoresis is mainly realized through the size-and/or density-based differences in the primary acoustic radiation force exerted on the particles, described by Equation (1 We previously demonstrated that lipid vesicles can undergo a reversible nodal or anti-nodal migration in a thermally-modulated ultrasonically-stimulated microfluidic channel. 185 The switch from nodal to anti-nodal focusing was determined to occur at a specific transition temperature attributed to a biomechanical transition in the stiffness of vesicles as the lipid membrane undergoes a thermotropic transition from an ordered "gel" phase to a disordered "fluid" phase.…”
Section: Introductionmentioning
confidence: 99%